Cochrane corner: rapid point-of-care antigen and molecular-based tests for the diagnosis of COVID-19 infection - Ndwandwe, Duduzile (Pan Afr Med J, 2020)
INTRODUCTION: the COVID-19 pandemic, which results from infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), presents important diagnostic challenges. Diagnostic strategies available to identify or rule out current infection, or to identify people in need of care escalation, or to test for past infection and immune response have become available, to reduce household and community transmission. We highlight a Cochrane review, published in September 2020, on the assessment of diagnostic accuracy of point-of-care antigen and molecular-based tests to determine current SARS-CoV-2 infection. METHODS: the authors of the Cochrane review searched multiple electronic databases for studies, which assessed SARS-CoV-2 infection with a diagnostic test. Eligible participants for the review included people with suspected current SARS-CoV-2 infection, known to have, or not to have COVID-19 infection, or where tests were used to screen for infection. RESULTS: the authors included 18 studies of point-of-care tests conducted in various parts of the world, with none from Africa. The review shows that there is considerable variability in sensitivity and specificity of the antigen tests. The review also shows that molecular tests had less variability in sensitivity and specificity. CONCLUSION: the review suggests that the current evidence is not strong enough to determine the usefulness of point-of-care tests in all settings. However, the benefits are likely to be more noticeable in countries, like Africa where community transmission is high. An impact evaluation would be warranted when rapid point-of-care tests are implemented in African countries.